The New Capital Adequacy Framework : Institutional Constraints and Incentive Structures - Karacadag, Cem.; Taylor, Michael (Washington, D.C. : International Monetary Fund, 2000)
This paper considers the implementation challenges facing the Basel Committee's new proposals on bank capital standards. When compared with the existing Capital Accord, the proposals represent a shift across two intersecting dimensions-regulatory versus economic capital, and rules-based versus process-oriented regulation. On minimum capital standards, the case for using external ratings may be stronger than has been recognized, given the divergences in the purpose and design of internal ratings. On supervisory review, ensuring comparability among supervisors and building supervisory capacity will present serious challenges. On enhancing market discipline, incentives for markets to exercise discipline will be required.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet